The concept of love: methodological aspects of philosophical and religious analysis - Конотоп, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The paper analyzes the concept of love in two Western European and Slavic traditions, especially in the culture of the Balkan region.Traced the formation of the concept of love in Ancient, Medieval, Renaissance, New time. It is noted that the days of antiquity and theMiddle Ages can be detected two trends in the interpretation problems of love – rationalist and existential. Particular attention is paid tothe culture of the XX-XXI centuries. In which love is directly linked to the outside boundary experience of the transcendent.